The Influence Of Electronic Word Of Mouth On Purchasing Decisions With Customer Reviews As A Moderating Variable - Daud, Anshar; Marasabessy, Nabila Cecilia; Utami, Eva Yuniarti; Hulu, Fatolosa; Baene, Eduar (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
ABSTRACT Researchers believe that word of mouth communication carried out online can influence employee purchasing decisions because it can attract the enthusiasm of other consumers and has broad, even infinite boundaries. Apart from that, researchers also believe that this influence will be more significant if it is accompanied by good customer reviews. Therefore, the research aims to analyze the influence of the Electronic-Word of Mouth variable on Purchasing Decisions with Customer Reviews as a moderating variable. This research is quantitative research with an explanatory approach. The data used in this research was distributed using an online questionnaire method to 100 sellers on TikTok and 200 consumers on TikTok with the minimum criteria of having shopped once. The questionnaire contains 14 question items containing statements of agree, strongly agree, normal, disagree, and strongly disagree on a number of questionnaires asked. This data can also be called primary data. The collected data was analyzed using the smart PLS 4.0 analysis tool. The result in this this research show word of mouth communication using the internet has its own advantages in increasing consumer purchasing decisions due to its wide reach, as informative material for consumers who are not familiar with the product, and increasing consumer enthusiasm. In line with this, the results of the first researcher's hypothesis and beliefs show that the Electronic Word of Mouth variable has a positive relationship and has a significant influence on purchasing decisions because the P-Values value is positive and is below the significance level of 0.05, namely 0.002. The second belief and also the second hypothesis in this research shows that good reviews from consumers can increase the influence of Word of Mouth Communication via the internet on Consumer Purchasing Decisions due to Word of Mouth Communication with quality product information, a comfortable place, and good service. from Consumer Reviews can make that influence even more significant. This can be proven from the results of the second hypothesis which shows the direction of the relationship is positive and the influence is more significant, namely 0.000 below 0.05, which is more significant than direct testing, namely 0.003. Thus, the first and second hypotheses in this research can be proven and accepted.